Bicyclo[6.1.0]nonyne carboxylic acid for the production of stable molecular probes. Issue 58 (17th November 2021) - Rady, Tony; Mosser, Michel; Nothisen, Marc; Erb, Stephane; Dovgan, Igor; Cianférani, Sarah; Wagner, Alain; Chaubet, Guilhem
Abstract : We report a novel strained alkyne, coined BCN acid. This compound participates efficiently in diverse bioorthogonal reactions and allows the facile production of amide probes, which showed superior in vitro stability compared to carbamate analogues. Abstract : Bicyclo[6.1.0]non-4-yn-9-ylmethanol (BCN alcohol) is the most prominent strained-alkyne scaffold in chemical biology. Described herein is the synthesis of an oxidized analogue – BCN acid – whose facile functionalization via amide bond formation yields more stable derivatives than the classically encountered carbamates.